Air flow characteristics of an air-assisted sprayer through horizontal crop canopy - Gupta, Pankaj; Sirohi, N. P. S.; Mishra, I.M. (International Journal of Agricultural and Biological Engineering, 2012)
Abstract: Artificially induced air currents or air-assistance to droplet spectrum produced by hydraulic nozzles not only facilitate in transporting and depositing the droplets in different parts of canopy but also reduce the application rate of chemicals. The air streams increase the velocity of smaller droplets so that extra momentum would increase impaction and improve penetration into the crop as well as mitigating the influence of wind on drift. It is necessary to quantify the airflow characteristics. But, control of climatic and other conditions in the field is very difficult. Thus, airflow characteristics study was done under controlled conditions on a horizontal simulated crop canopy. Based on this study, an airflow distribution model was developed and airflow characteristics for vegetable crops, namely, eggplant, chilli and bittergourd were predicted. The differences between predicted and actual field study values were not statistically significant. Kinetic energy of air stream dissipated with its movement from top to bottom of the canopy. The rate of kinetic energy dissipation was higher in denser canopies. Higher air velocity 15 m/s was the best as it produced maximum turbulence throughout the canopy.Keywords: air assisted sprayer, simulated crop canopy, air velocityDOI: 10.3965/j.ijabe.20120501.001Citation: Pankaj Gupta, Sirohi N P S, Mishra I M. Air flow characteristics of an air-assisted sprayer through horizontal crop canopy. Int J Agric & Biol Eng, 2012; 5(1): 1